Nutritional composition of pre-dried silage of different winter cereals - Horst, Egon Henrique; Neumann, Mikael; Mareze, Juliana; Leão, Guilherme Fernando Mattos; Bumbieris Junior, Valter Harry; Mendes, Marcelo Cruz (Acta Scientiarum. Animal Sciences, 2018)
This study aimed to assess the chemical composition of the forage and pre-dried silage from twelve winter cereals harvested at pre-flowering. We used black oat (Avena strigosa) cv. EMB 139 and cv. IAPAR 61; white oat (Avena sativa) cv. IPR and 126 hp. URS Taura; barley (Hordeum vulgare) cv. BRS Brau and cv. BRS Cauê; wheat (Triticum aestivum) cv. BRS Umbu and cv. BRS Tarumã; rye (Secale cereale) cv. Temprano and cv. BRS Serrano; and triticale (X. Triticosecale) cv. IPR and 111 hp. BRS Saturno. Plants were harvested at pre-flowering, when they were pre-dried and ensiled. The analysis of variance evidenced nutritional differences between species and cultivars. Triticale cv. IPR 111 showed notorious chemical characteristics in relation to the other treatments, highest protein content (113.7 g kg-1) and lower content of NDF and ADF (657.9 and 380.9 g kg-1, respectively). Among the pre-dried silages, barley cv. BRS Cauê had the highest level of NDT (614.7 g kg-1). Triticale cv. IPR 111 was shown as a high-quality nutritional food as forage and kept these characteristics after conservation. On the other hand, the pre-dried silage of barley cv. BRS Cauê showed the highest potential for nutrient degradability.